Qur’anic Philanthropy as Social Ethics: A Study of Ṣadaqah in the Qur’an - Basri Mahmud; Fauziah Fauziah; Mujahid Mujahid; Hardivizon Hardivizon; Muhammad Zakir Husain (ZAD Al-Mufassirin, 2026)
This study aims to analyze the concept of ṣadaqah in the Qur’an as an integral component of Qur’anic philanthropy and to examine its role in constructing the framework of Islamic social ethics. It employs a library research method using a thematic exegesis (tafsīr mawḍū‘ī) approach and the perspective of Islamic social ethics. The primary data consists of Qur’anic verses concerning ṣadaqah, which are analyzed through classical and contemporary Qur’anic exegeses and further enriched with academic literature on Islamic philanthropy, social justice, and Islamic social ethics. The findings demonstrate that ṣadaqah in the Qur’an functions not only as an individual spiritual act of worship but also as a moral and social instrument aimed at strengthening social solidarity, protecting vulnerable groups, and promoting the distribution of welfare within society. The Qur’an positions ṣadaqah as a mechanism of ethical redistribution that challenges the concentration of wealth and emphasizes social responsibility as an integral dimension of religious life. The study concludes that Qur’anic philanthropy constitutes a foundational framework of Islamic social ethics that integrally unites spirituality, morality, and social justice, while remaining highly relevant to addressing contemporary problems of inequality and the erosion of social solidarity.